To study the effect of various combinations of haart in CD4+ cell count in HIV patient at RIMS, Ranchi Art Centre - Mahato, Sumit Kumar; Prasad Keshri, Uma Shanker; Kumar, Akhilesh; Protim, Pholgu; Kumar, Vineet (International Journal of Basic & Clinical Pharmacology, 2017)
Background: India has the third largest HIV epidemic in the world. In 2013, HIV prevalence in India was an estimated 0.3%, an estimated 130,000 people died from AIDS-related illnesses. Overall, India’s HIV epidemic is slowing down, with a 19% decline in new HIV infections (130,000 in 2013), and a 38% decline in AIDS-related deaths between 2005 and 2013. Antiretroviral therapy (ART) for the treatment of HIV infection has improved steadily since the advent of potent combination therapy in 1996. ART has dramatically reduced HIV-associated morbidity and mortality. The aim of this study is to see the change in CD4+ count in patient taking various combination of HAART (Highly active anti-retroviral treatment). Methods: A total of 215 patients were included in this study that came to the rims art centre for regular follow up and there cd4+ count at 6 monthly interval upto 18 months was taken and analysed. Results: The patients were evaluated for their change in CD4+ cell count. Mean of CD4+ count at 6 monthly interval was taken in this study which showed that haart combination causes significant improvement in cd4+ count in each group (1) stavudine, lamivudine, nevirapine (2)stavudine, lamivudine, efavirenz (3) zidovudine, lamivudine, nevirapine (4) zidovudine, lamivudine, efavirenz, (5) tenofovir, lamivudine, efavirenz. Conclusions: SLN combination was found most effective in increasing the CD4+ Cell count in comparision to the other combination. Other drugs combinations in decreasing order are as follows- SLE, ZLE, TLE, ZLN.